Low intensity mechanical signals promote proliferation in a cell-specific manner: Tailoring a non-drug strategy to enhance biomanufacturing yields - M. Ete Chan; Christopher Ashdown; Lia Strait; Sishir Pasumarthy; Abdullah Hassan; Steven Crimarco; Chanpreet Singh; Vihitaben S. Patel; Gabriel Pagnotti; Omor Khan; Gunes Uzer; Clinton T. Rubin (Mechanobiology in Medicine)
Biomanufacturing relies on living cells to produce biotechnology-based therapeutics, tissue engineering constructs, vaccines, and a vast range of agricultural and industrial products. With the escalating demand for these bio-based products, any process that could improve yields and shorten outcome timelines by accelerating cell proliferation would have a significant impact across the discipline. While these goals are primarily achieved using biological or chemical strategies, harnessing cell mechanosensitivity represents a promising – albeit less studied – physical pathway to promote bioprocessing endpoints, yet identifying which mechanical parameters influence cell activities has remained elusive. We tested the hypothesis that mechanical signals, delivered non-invasively using low-intensity vibration (LIV; <1 ​g, 10–500 ​Hz), will enhance cell expansion, and determined that any unique signal configuration was not equally influential across a range of cell types. Varying frequency, intensity, duration, refractory period, and daily doses of LIV increased proliferation in Chinese Hamster Ovary (CHO)-adherent cells (+79% in 96 ​hr) using a particular set of LIV parameters (0.2 ​g, 500 ​Hz, 3 ​× ​30 ​min/d, 2 ​hr refractory period), yet this same mechanical input suppressed proliferation in CHO-suspension cells (−13%). Another set of LIV parameters (30 ​Hz, 0.7 ​g, 2 ​× ​60 ​min/d, 2 ​hr refractory period) however, were able to increase the proliferation of CHO-suspension cells by 210% and T-cells by 20.3%. Importantly, we also reported that T-cell response to LIV was in-part dependent upon AKT phosphorylation, as inhibiting AKT phosphorylation reduced the proliferative effect of LIV by over 60%, suggesting that suspension cells utilize mechanism(s) similar to adherent cells to sense specific LIV signals. Particle image velocimetry combined with finite element modeling showed high transmissibility of these signals across fluids (>90%), and LIV effectively scaled up to T75 flasks. Ultimately, when LIV is tailored to the target cell population, it's highly efficient transmission across media represents a means to non-invasively augment biomanufacturing endpoints for both adherent and suspended cells, and holds immediate applications, ranging from small-scale, patient-specific personalized medicine to large-scale commercial bio-centric production challenges.